Historic and Contemporary Land Use Shape Plant-Pollinator Networks and Community Composition - Cortina, Camila A.; Neff, John L.; Jha, Shalene (Frontiers in Ecology and Evolution, 2022)
Globally, grasslands represent a critical but shrinking habitat for native plants and pollinators, with declines driven by alterations to landscape-scale habitat cover and local-scale disturbance regimes, among other factors. Specifically, as cities expand in size, an increasing proportion of regional pasture and grassland habitat is being replaced by urban development, and fewer periodic grazing and burning regimes are being supported locally, despite evidence that such regimes promote plant species richness and facilitate their interaction with native pollinators. The quantification of these plant-pollinator networks—through indices such as network connectance, specialization, nestedness, and robustness—can provide a unique opportunity to characterize key structural properties of species interactions and their response to human management and seasonal phenology. While urbanization and local disturbance regimes likely influence plant and pollinator communities and their interactions, past research in this area has primarily been conducted at limited spatial and temporal scales and has not typically quantified the impacts of both local and landscape forces on network properties. In this study, we investigate the effects of contemporary (past 10 years) and historic (prior 90 years) disturbance regimes on plant-pollinator community composition and network structure across more than 200 km of grassland in Central Texas. Our analyses indicate that for plant and pollinator communities, both contemporary and historic land management practices have led to significantly dissimilar community composition. Plant and pollinator richness and network nestedness are negatively correlated with phenological period, while pollinator richness is positively correlated with landscape-scale (2 km) urbanized land cover and is higher in historically grazed land, likely due to greater food and nesting resource availability. In contrast, we show that network connectance is positively correlated with phenological period and negatively correlated with landscape-scale urban cover. Finally, we show that pollinator robustness, a measure of resilience to plant species loss, is positively correlated with landscape-scale urbanization, likely due to greater redundancy provided by common weedy plant species. Overall, our results demonstrate that historic grazing regimes, current urbanization levels, and distinct phenological periods can simultaneously drive plant-pollinator community composition and network dynamics in shrinking but critical grassland ecosystems.